Study on particle fragmentation characteristics during rapid pyrolysis of coal based on the structural characteristics of coal macerals - Guoping Ma; Peng Lv; Xudong Song; Yonghui Bai; Jiaofei Wang; Weiguang Su; Guangsuo Yu (Fuel, 2026)

A decision-support framework for balancing growth, profit and environmental impacts in aquaculture feeding - Chunlin Chen; Youbang Guan; Lihua Song; Guoping Lian; Daoliang Li; Ran Zhao; Lian X. Liu; Michael Short (Aquacultural Engineering, 2026)

Osteoprotective effect of Perinereis aibuhitensis ultrasound-assisted aqueous extract against retinoic acid-induced osteoporosis in mice - Biliang Mo; Xinxia Song; Jianmeng Liao; Xiaoyu Xia; Hongyu Lu; Wenhong Cao; Zhongqin Chen; Mingtang Tan; Huina Zheng; Jialong Gao; Haisheng Lin; Zhihong Zheng; et al. (Food Bioscience, 2026)

Modeling ammonia nitrogen dynamics coupled with fish growth physiology in recirculating aquaculture systems - Lihua Song; Yingyi Chen; Daoliang Li; Chunlin Chen; Liang Wang; Tao Chen; Guoping Lian (Aquacultural Engineering, 2026)

Bioengineering extracellular vesicles for enhanced therapeutic functionality and clinical potential in the cardiovascular system - Yongtao Wang; Meiyu Hu; Michail Spanos; Shihui Xu; Jiaxin Song; Guoping Li; Dragos Cretoiu; Junjie Xiao (Science Bulletin, 2026)

A 500-year cycle of demographic expansion and contraction in the lower Yangtze and adjacent coastal region during the Holocene driven by East Asian summer monsoon oscillations - Deke Xu; Yuhai Wang; Keyang He; Hao Li; Yajie Dong; Jun Kuang; Zhigang Zhang; Bing Song; Yulong Niu; Guoping Sun; Yonglei Wang; Jiatong Lu; et al. (Quaternary Science Reviews, 2026)

Periplasmic transport channels to accelerate the proton motive force for efficient groundwater bioelectrocatalytic Cr(VI) reduction - Huajing Zhou; Kun Wang; Liang He; Zilian Liu; Dianchao Kong; Qiang Zhang; Song Jin; Ying Han; Qingqing Guan; Guoping Sheng (Water Research, 2026)

Role of the AMPK/PGC-1α/SIRT3-Mediated Mitochondrial Dysfunction in the Neurotoxicity of Methanol - Xiaojie Han; Mengnan Peng; Xinqiao Wang; Yundi Hu; Guoping Li; Yanan Song; Yanling Lv; Nan Chen (Molecular Neurobiology, 2026)

Urban trash bins as reservoirs of multidrug-resistant Enterococcus with shared resistance genes across clinical and environmental niches - Jie Li; Xiaorui Mao; Yu Song; Xiaohe Hu; Guoping Zhao; Biao Tang (Journal of Hazardous Materials, 2025)

Dynamically programmable plant-derived scaffold coordinates alveolar bone repair cascade: Phase-adaptive integration from hemostasis to bone remodeling - Yeke Chen; Yumei Ning; Fang Dai; Yuting Yang; Chenjiang He; Kaiqiang Yang; Yichen Hu; Guoping Cheng; Li Song (Chemical Engineering Journal, 2025)

Exploring the trade-offs and synergies among ecosystem services to support ecological management in the Yangtze River Delta Urban Agglomeration - Song Yao; Yonghua Li; Xiangyang Quan; Guoping Huang; Jiren Xu (Journal of Environmental Management, 2025)

Combined influence of strong winds and warm deep water on the formation of Amundsen Sea Polynya in winter - Mengting Zhuo; Yu Hong; Yuhong Zhang; Jiping Liu; Lingqiao Cheng; Guoping Zhu; Song Hu; Yan Du (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Recent advances in taste transduction mechanism, analysis methods and strategies employed to improve the taste of taste peptides - Chunyong Song; Zhijun Wang; Hanqi Li; Wenhong Cao; Zhongqin Chen; Huina Zheng; Jialong Gao; Haisheng Lin; Guoping Zhu (Critical Reviews in Food Science and Nutrition, 2025)

Preparation of cementing material and recovery of iron resources using converter slag - Shuai Hao; Guoping Luo; Lin Wang; Shengli An; Yifan Chai; Wei Song (Process Safety and Environmental Protection, 2024)

Efficient removal of phosphate and fluoride from phosphogypsum leachate by lanthanum-modified zeolite: Synchronous adsorption behavior and mechanism - Mengxuan Zhao; Xiaomeng Zhou; Junfeng Li; Fei Li; Xiaodi Li; Junxia Yu; Li Guo; Guoping Song; Chunqiao Xiao; Fang Zhou; Ruan Chi; Guoqing Feng (Journal of Environmental Chemical Engineering, 2024)

Highly efficient recovery of phosphate and fluoride from phosphogypsum leachate: Selective precipitation and adsorption - Mengxuan Zhao; Xiaodi Li; Jun-xia Yu; Fei Li; Li Guo; Guoping Song; Chunqiao Xiao; Fang Zhou; Ruan Chi; Guoqing Feng (Journal of Environmental Management, 2024)

Effect of baking on the structure and bioavailability of protein-binding zinc from oyster (Crassoetrea hongkongensis) - Chunyong Song; Runfang Zhong; Shan Zeng; Zhongqin Chen; Mingtang Tan; Huina Zheng; Jialong Gao; Haisheng Lin; Guoping Zhu; Wenhong Cao (Food Chemistry, 2024)

Evaluation of urban flood adaptability based on the InVEST model and GIS: A case study of New York City, USA - Song Yao; Guoping Huang; Zihan Chen (Natural Hazards, 2024)

Ocean-Mixer: A Deep Learning Approach for Multi-Step Prediction of Ocean Remote Sensing Data - Sai Wang; Guoping Fu; Yongduo Song; Jing Wen; Tuanqi Guo; Hongjin Zhang; Tuantuan Wang (Journal of Marine Science and Engineering, 2024)
The development of intelligent oceans requires exploration and an understanding of the various characteristics of the oceans. The emerging Internet of Underwater Things (IoUT) is an extension of the Internet of Things (IoT) to underwater environments, and the ability of IoUT to be combined with deep learning technologies is a powerful technology for realizing intelligent oceans. The underwater acoustic (UWA) communication network is essential to IoUT. The thermocline with drastic temperature and density variations can significantly limit the connectivity and communication performance between IoUT nodes. To more accurately capture the complexity and variability of ocean remote sensing data, we first sample and analyze ocean remote sensing datasets and provide sufficient evidence to validate the temporal redundancy properties of the data. We propose an innovative deep learning approach called Ocean-Mixer. This approach consists of three modules: an embedding module, a mixer module, and a prediction module. The embedding module first processes the location and attribute information of the ocean water and then passes it to the subsequent modules. In the mixing module, we apply a temporal decomposition strategy to eliminate redundant information and capture temporal and channel features through a self-attention mechanism and a multilayer perceptron (MLP). The prediction module ultimately discerns and integrates the temporal and channel relationships and interactions among various ocean features, ensuring precise forecasting. Numerous experiments on ocean temperature and salinity datasets show that Mixer-Ocean performs well in improving the accuracy of time series prediction. Mixer-Ocean is designed to support multi-step prediction and capture the changes in the ocean environment over a long period, thus facilitating efficient management and timely decision-making for innovative ocean-oriented applications, which has far-reaching significance for developing and conserving marine resources.

Synergistic leaching process for ion-exchange ammonium from weathered crust elution deposited rare earth tailings with potassium magnesium compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Guoping Song; Ze Ouyang; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Environmental Science and Pollution Research, 2023)

Formation of natural fractures and their impact on shale oil accumulation in the Mahu Sag, Junggar Basin, NW China - Xiaoyu Du; Zhijun Jin; Lianbo Zeng; Guoping Liu; Wenjun He; Mehdi Ostadhassan; Yong Song; Xinping Liang; Sen Yang; Guoqing Lu (International Journal of Coal Geology, 2023)

Natural fractures in ultra-deep reservoirs of China: A review - Lianbo Zeng; Yichen Song; Guoping Liu; Xiaolin Tan; Xiaotong Xu; Yingtao Yao; Zhe Mao (Journal of Structural Geology, 2023)

Mdivi-1 Modulates Macrophage/Microglial Polarization in Mice with EAE via the Inhibition of the TLR2/4-GSK3β-NF-κB Inflammatory Signaling Axis - Xiaoqin Liu; Xiaojuan Zhang; Xiaojie Niu; Peijun Zhang; Qing Wang; Xiuhua Xue; Guobin Song; Jiezhong Yu; Guoping Xi; Lijuan Song; Yanhua Li; Cungen Ma (Molecular Neurobiology, 2022)

Circulating microRNA-30a-5p, microRNA-101-3p, microRNA-140-3p and microRNA-141-3p as potential biomarkers for dexmedetomidine response in pediatric patients - Xinmei Cai; Bilian Li; Wei Wei; Yanping Guan; Xue Bai; Min Huang; Yaying Huang; Lili Rong; Xingrong Song; Guoping Zhong (European Journal of Clinical Pharmacology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A botanical medicine dragon’s blood exhibited clinical antithrombosis efficacy similar to low molecular weight heparin - Jiangbin Liang; Song Mei; Xiangyu Qiao; Wei Pan; Yan Zhao; Shaohui Shi; Yaling Zhai; Haizhao Wen; Guoping Wu; Chengyu Jiang (Science China Life Sciences, 2021)

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Homeobox Gene Six3 is Required for the Differentiation of D2-Type Medium Spiny Neurons - Xiaolei Song; Haotian Chen; Zicong Shang; Heng Du; Zhenmeiyu Li; Yan Wen; Guoping Liu; Dashi Qi; Yan You; Zhengang Yang; Zhuangzhi Zhang; Zhejun Xu (Neuroscience Bulletin, 2021)
Medium spiny neurons (MSNs) in the striatum, which can be divided into D1 and D2 MSNs, originate from the lateral ganglionic eminence (LGE). Previously, we reported that Six3 is a downstream target of Sp8/Sp9 in the transcriptional regulatory cascade of D2 MSN development and that conditionally knocking out Six3 leads to a severe loss of D2 MSNs. Here, we showed that Six3 mainly functions in D2 MSN precursor cells and gradually loses its function as D2 MSNs mature. Conditional deletion of Six3 had little effect on cell proliferation but blocked the differentiation of D2 MSN precursor cells. In addition, conditional overexpression of Six3 promoted the differentiation of precursor cells in the LGE. We measured an increase of apoptosis in the postnatal striatum of conditional Six3 -knockout mice. This suggests that, in the absence of Six3, abnormally differentiated D2 MSNs are eliminated by programmed cell death. These results further identify Six3 as an important regulatory element during D2 MSN differentiation.

Big Data Nanoindentation and Analytics Reveal the Multi-Staged, Progressively-Homogenized, Depth-Dependent Upscaling of Rocks’ Properties - Shengmin Luo; Daeyoung Kim; Yongkang Wu; Yucheng Li; Dongfang Wang; Jinliang Song; Don J. DeGroot; Guoping Zhang (Rock Mechanics and Rock Engineering, 2021)

Multiple steps determine CD73 shedding from RPE: lipid raft localization, ARA1 interaction, and MMP-9 up-regulation - Wei Zhang; Shumin Zhou; Guoping Liu; Fanqiang Kong; Song Chen; Hua Yan (Purinergic Signalling, 2018)

Inferring trophic variation for Antarctic krill (Euphausia superba) in the Antarctic Peninsula from the austral fall to early winter using stable isotope analysis - Guoping Zhu; Haiting Zhang; Qi Song; Yang Yang; Shaoqin Wang; Qingyuan Yang (Acta Oceanologica Sinica, 2018)

A Metric Model on Identifying the National Water Scarcity Management Ability - Yue Chen; Guoping Cen; Chuanping Hong; Jiying Liu; Song Lu (Water Resources Management, 2018)

ZIKA virus isolated from mosquitoes: a field and laboratory investigation in China, 2016 - Shihong Fu; Song Song; Hong Liu; Yuanyuan Li; Xiaolong Li; Xiaoyan Gao; Ziqian Xu; Guoping Liu; Dingming Wang; Zhenzao Tian; Jingzhu Zhou; Ying He; et al. (Science China Life Sciences, 2017)

Bisphenol A Represses Dopaminergic Neuron Differentiation from Human Embryonic Stem Cells through Downregulating the Expression of Insulin-like Growth Factor 1 - Boxian Huang; Song Ning; Qinjing Zhang; Aiqin Chen; Chunyan Jiang; Yugui Cui; Jian Hu; Hong Li; Guoping Fan; Lianju Qin; Jiayin Liu (Molecular Neurobiology, 2017)

Uncertainty in air–sea CO 2 flux due to transfer velocity - Tan Yu; Yijun He; Jinbao Song; Hui Shen; Juanjuan Wang; Guoping Gao (International Journal of Remote Sensing, 2014)

Codon Optimization Enhances Protein Expression of Bombyx mori Nucleopolyhedrovirus DNA Polymerase in E. coli - Huifang Song; Guohui Li; Weijun Mai; Guoping Huang; Keping Chen; Yajing Zhou; Huiqing Chen (Current Microbiology, 2014)

Molecular and serological diversity in Apple chlorotic leaf spot virus from sand pear (Pyrus pyrifolia) in China - Yansu Song; Ni Hong; Liping Wang; Hongju Hu; Rui Tian; Wenxing Xu; Fang Ding; Guoping Wang (European Journal of Plant Pathology, 2011)

Reproductive biology of yellowfin tuna T. albacares in the west-central Indian Ocean - Guoping Zhu; Liuxiong Xu; Yingqi Zhou; Liming Song (Journal of Ocean University of China, 2008)